2018 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2018
DOI: 10.1109/pesgm.2018.8586529
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Hardware-In-The-Loop Comparison of Frequency Estimation Techniques in Application to ROCOF Based Islanding Detection

Abstract: Rate of change of frequency (ROCOF) is one of the most common islanding detection techniques because of its simplicity and economical benefits. However, it does need thorough considerations to avoid mis-operations of ROCOF relays during islanding. These relays operates based on frequency estimation, which is performed either from the phase voltages or by obtaining the speed measurement from generator. With the penetration of distributed generation (DG), there is high probability for unavailability of frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several authors have investigated the possible challenges when measuring the RoCoF since its behaviour might determine a possible loss of stability or poorly control performance. A study showing the impact of the RoCoF location measurements is shown in [16], the susceptibility of RoCoF measurements to common power system disturbances such as phase steps is described in [17], the settings of RoCoF relays during islanding are studied in [18], an on-line frequency estimator is proposed in [19], and implementing a digital filter and consecutive data-points for inertia estimation and a comparison of frequency estimation techniques are explored in [20]. A study of several variations of PLL for PMU application is presented in [21], investigating the update rate of frequency and RoCoF measurements with high accuracy under off-nominal frequency scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the possible challenges when measuring the RoCoF since its behaviour might determine a possible loss of stability or poorly control performance. A study showing the impact of the RoCoF location measurements is shown in [16], the susceptibility of RoCoF measurements to common power system disturbances such as phase steps is described in [17], the settings of RoCoF relays during islanding are studied in [18], an on-line frequency estimator is proposed in [19], and implementing a digital filter and consecutive data-points for inertia estimation and a comparison of frequency estimation techniques are explored in [20]. A study of several variations of PLL for PMU application is presented in [21], investigating the update rate of frequency and RoCoF measurements with high accuracy under off-nominal frequency scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the technical literature, different frequency estimation might result in different frequency estimates. Additionally, digital relays filter the input and output signals to reduce the influence of distortions, which might cause signal attenuation or time delay (Sorrentino and Carvalho, 2010;Sanca, Souza and Costa, 2016;Grebla, Yellajosula and Hoidalen, 2018). Thus, frequency protections using different estimation methods can produce different results.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the ROCOF relay of SDG, which is the most widely used device for islanding detection among the frequency‐based relays [2, 5, 26], is adjusted by an approach utilising the particle swarm optimisation (PSO) algorithm as well as AR and PIAR. Unlike [6, 2224], in which AR and/or PIAR are(is) obtained by conducting numerous dynamic simulations, this paper uses analytical formulas to form AR and PIAR, making the relay adjustment process much faster and more convenient.…”
Section: Introductionmentioning
confidence: 99%